Analyzing non-English major students’ needs, attitudes, and English language learning strategies - Sari, Farnia; Atmanegara, Yunani; Manurung, Jenny Elvinna; Ali, Helena Verusha; Amaliah, Amaliah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Students learn English with different educational backgrounds at university level. Through this course, students can get the opportunity to develop their English competence for their learning success and future professional needs. To maximise the attainments of the goals, ESP teachers need to design ESP courses relevant to the students’ needs and conditions. This study surveyed 180 non-English major students to investigate their needs in learning English, learning attitude, and language learning strategies. The results reveal students still lacking in all English skills and language use. Therefore, ESP teachers should provide learning materials and inputs that can develop students’ English competence. ESP teachers need to struggle to make non-English major students hold a positive attitude toward English language learning. This finding showed that even though the students had confidence and motivation in learning English, they felt anxious and insecure during the teaching and learning process. Since this study involved non-English major students from different educational backgrounds, it was found that students’ language learning strategies were various. The results did not show certain strategies used by the students in learning English in higher education. ESP teachers should provide a variety of teaching techniques that can help students maximise their English language learning.